Buddhism and quantum physics: Generality - Yupapin, Preecha (International Journal of Scientific World, 2015)
The generalized concept of Buddhism is presented in terms quantum physics, which can be used to practice and reach the noble human life, where the related Buddhism principles can be formulated by the quantum physics concept. This can lead to meet the well-known Buddhism practical states, where they are the contemplation and perception. Finally, the zero energy state (nirvana) can be achieved and realized, which is benefit to the un-limited brain performance condition and discussed.